Relación escuela - comunidad :El caso de la escuela Simón Bolívar de la Comunidad Santo Domingo No. 2 Ayora - Cayambe - Ulcuango Túquerres, Luis Patricio (1997)
Introduction. The intercultural bilingual education in Ecuador. School and indigenous community. Formal education vs Community Culture. Education and community integration. Divorce School and community. Conclusions. Bibliography.